Archaeological sites outside the walls of Ptolemais - Abd Rabbo, Muftah Othman (Al-Mukhtar Journal of Social Sciences, 2010)
The city of Ptolemais was founded, according to available classical sources, as a port for the city of Cyrene. No name for this settlement is known prior to the 4th century BCE when it was referred to as the port of Cyrene, a name mentioned by the classical writer Skylax in the late 4th century BCE. It is possible that some Greek settlers who founded the city of Cyrene directed themselves to this location, which is the most suitable and geographically closest in the coastal region between Tokra and Al-Aqlah. Excavations revealed pottery fragments dating back to the early Greek colonization period (between 620 and 600 BCE). The available data currently supports the view that the ancient name of Ptolemais was Cyrene, suggesting a very close connection between the two cities to the extent that it is difficult to distinguish between them. During the reign of Emperor Diocletian (293-305 CE), Ptolemais became the new capital of the province of Upper Libya. It served as the residence for Christian bishops, including notable figures like the priest Synesius. Ptolemais remained the capital of the region until the mid-5th century AD. In this research, we aim to highlight the most significant archaeological sites outside the walls of Ptolemais and their relationship to the city.
Keywords: Ptolemais; Cyrenaica; Greek settlers